Small Molecule Mediated Restoration of Mitochondrial Function Augments Anti-Mycobacterial Activity of Human Macrophages Subjected to Cholesterol Induced Asymptomatic Dyslipidemia - Asalla, Suman; Mohareer, Krishnaveni; Banerjee, Sharmistha (Frontiers in Cellular and Infection Microbiology, 2017)
Mycobacterium tuberculosis (M.tb) infection manifests into tuberculosis (TB) in a small fraction of the infected population that comprises the TB susceptible group. Identifying the factors potentiating susceptibility to TB persistence is one of the prime agenda of TB control programs. Recently, WHO recognized diabetes as a risk factor for TB disease progression. The closely related pathological state of metabolic imbalance, dyslipidemia, is yet another emerging risk factor involving deregulation in host immune responses. While high cholesterol levels are clinically proven condition for perturbations in cardiac health, a significant fraction of population these days suffer from borderline risk cholesterol profiles. This apparently healthy population is susceptible to various health risks placing them in the “pre-disease” range. Our study focuses on determining the role of such asymptomatic dyslipidemia as a potential risk factor for susceptibility to TB persistence. Macrophages exposed to sub-pathological levels of cholesterol for chronic period, besides impaired release of TNF-α, could not clear intracellular pathogenic mycobacteria effectively as compared to the unexposed cells. These cells also allowed persistence of opportunistic mycobacterial infection by M. avium and M. bovis BCG, indicating highly compromised immune response. The cholesterol-treated macrophages developed a foamy phenotype with a significant increase in intracellular lipid-bodies prior to M.tb infection, potentially contributing to pre-disease state for tuberculosis infection. The foamy phenotype, known to support M.tb infection, increased several fold upon infection in these cells. Additionally, mitochondrial morphology and function were perturbed, more so during infection in cholesterol treated cells. Pharmacological supplementation with small molecule M1 that restored mitochondrial structural and functional integrity limited M.tb survival more effectively in cholesterol exposed macrophages. Mechanistically, M1 molecule promoted clearance of mycobacteria by reducing total cellular lipid content and restoring mitochondrial morphology and function to its steady state. We further supported our observations by infection assays in PBMC-derived macrophages from clinically healthy volunteers with borderline risk cholesterol profiles. With these observations, we propose that prolonged exposure to sub-pathological cholesterol can lead to asymptomatic susceptibility to M.tb persistence. Use of small molecules like M1 sets yet another strategy for host-directed therapy where re-functioning of mitochondria in cholesterol abused macrophages can improve M.tb clearance.